1999
DOI: 10.1136/thx.54.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of differing doses of inhaled budesonide on markers of airway inflammation in patients with mild asthma

Abstract: Background-It is desirable to prescribe the minimal eVective dose of inhaled steroids to control asthma. To ensure that inflammation is suppressed whilst using the lowest possible dose, a sensitive and specific method for assessing airway inflammation is needed. Methods-The usefulness of exhaled nitric oxide (NO), sputum eosinophils, and methacholine airway responsiveness (PC 20 ) for monitoring airway inflammatory changes following four weeks of treatment with an inhaled corticosteroid (budesonide via Turboha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
166
2
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(190 citation statements)
references
References 31 publications
15
166
2
7
Order By: Relevance
“…To date, the dose-dependent effect of ICS on airway eosinophilia has mainly been assessed on induced sputum samples. These studies also indicate that ICS are effective, from low doses onwards, at reducing eosinophil number, and that the dose-response curve is relatively flat [17][18][19][20]. To what extent this is paralleled by changes in mucosal eosinophil number has not been fully established in humans.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To date, the dose-dependent effect of ICS on airway eosinophilia has mainly been assessed on induced sputum samples. These studies also indicate that ICS are effective, from low doses onwards, at reducing eosinophil number, and that the dose-response curve is relatively flat [17][18][19][20]. To what extent this is paralleled by changes in mucosal eosinophil number has not been fully established in humans.…”
Section: Discussionmentioning
confidence: 94%
“…Adopting the latter strategy meant that the subjects were treated with a mean additional dose of 400 mg of ICS over a 2-yr treatment period. Also, JATAKANON et al [17] demonstrated that only a dose of 1,600 mg budesonide was sufficient to decrease methacholine airway responsiveness, whereas 400 mg was sufficient to reduce exhaled nitric oxide levels and sputum eosinophil number. These observations illustrate that the mechanisms underlying AHR are relatively resistant to steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, all patients in the current stable asthma group were taking regular inhaled corticosteroids, and in steroid-treated patients the relationship between NO and sputum eosinophils is much less pronounced [27,28]. These two markers vary in their response to inhaled steroid treatment [30,31]. EBC pH has previously been reported to correlate with sputum eosinophils in asthma by KOSTIKAS et al [32].…”
Section: Discussionmentioning
confidence: 99%
“…AHR is a fundamental component of the definition of asthma, and has been associated with asthma exacerbations [23], airway inflammation [24] and decline in lung function [25]. Previous studies have shown a dose-dependent improvement in AHR with inhaled corticosteroid treatment [26,27], and asthma outcomes and basement membrane thickness improved when AHR was added to a treatment algorithm [7]. A recent study by MEIJER et al [11] showed that high-dose fluticasone was more effective in improving AHR than oral prednisolone.…”
Section: Discussionmentioning
confidence: 99%